2001
DOI: 10.1016/s0376-6357(01)00135-8
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons’ timing of an arbitrary and a naturalistic auditory stimulus: tone versus cooing

Abstract: Previous animal research has traditionally used arbitrary stimuli to investigate timing in a temporal bisection procedure. The current study compared the timing of the duration of an arbitrary, auditory stimulus (a 500-Hz tone) to the timing of the duration of a naturalistic, auditory stimulus (a pigeon cooing). In the first phase of this study, temporal perception was assessed by comparing psychophysical functions for the duration of tone and cooing signals. In the first set of tests, the point of subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…In particular, group filled-first demonstrated a robust CLE with empty intervals, as is the case in the absence of prior training with filled intervals (group empty-first in Experiment 1; Grant, 2001;Santi et al, 2003;Santi et al, 1999). Fourth, the PSE on empty trials approximates the geometric mean of the short (2-sec) and the long (8-sec) samples, as is typically the case with filled intervals (e.g., Gibbon, 1986;Miki & Santi, 2001;Spetch & Wilkie, 1983;Stubbs, 1968). Hence, although retention is strongly affected by whether an interval is empty or filled, the mechanisms of timing that interval appear not to be so affected.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In particular, group filled-first demonstrated a robust CLE with empty intervals, as is the case in the absence of prior training with filled intervals (group empty-first in Experiment 1; Grant, 2001;Santi et al, 2003;Santi et al, 1999). Fourth, the PSE on empty trials approximates the geometric mean of the short (2-sec) and the long (8-sec) samples, as is typically the case with filled intervals (e.g., Gibbon, 1986;Miki & Santi, 2001;Spetch & Wilkie, 1983;Stubbs, 1968). Hence, although retention is strongly affected by whether an interval is empty or filled, the mechanisms of timing that interval appear not to be so affected.…”
Section: Discussionmentioning
confidence: 73%
“…The PSE is the sample duration at which pigeons are indifferent between short and long and are equally likely to respond short as to respond long to that duration. A number of studies using filled intervals have revealed that the PSE falls at the geometric mean between the short and the long samples (e.g., Gibbon, 1986;Miki & Santi, 2001;Spetch & Wilkie, 1983;Stubbs, 1968). The geometric mean is computed as the square root of the product of the short and the long durations.…”
Section: Methodsmentioning
confidence: 99%
“…For example, both humans' and other animals' duration discriminations in this range are characterized by the scalar property, and both humans and other animals are able to time multiple stimuli in a flexible manner (e.g., Boisvert & Sherry, 2006; Buhusi, Sasaki, & Meck, 2002; Gallistel, King, & McDonald, 2004; Henderson, Hurly, Bateson, & Healy, 2006; Higa & Simm, 2004; Lejeune & Wearden, 2006; Malapani & Fairhurst, 2002; Paule et al, 1999). Consequently, interval-timing tasks such as the bisection procedure are excellent candidates for investigating decision and memory processes because they can be implemented in a functionally equivalent manner across a wide variety of animal species and conditions (e.g., Allan & Gibbon, 1991; Church & Deluty, 1977; Meck, 1991; Miki & Santi, 2001; Stubbs, 1976; Wearden & Ferrara, 1995, 1996).…”
mentioning
confidence: 99%
“…Wearden 等 (Wearden & Culpin, 1998;Wearden & Ferrara, 1993;Wearden, Goodson, & Foran, 2007;Wearden, Parry, & Stamp, 2002)以人为被试, 采用 Wearden 和 Ferrara(1993)的"变动-标准"(roving-standard)法, 发现不同刺激通道和不同刺激类型时 间的短时保持都呈现出主观缩短。 与主观缩短现象相反, 一些动物研究则发现延 迟判断呈现主观变长(subjective lengthening)。Santi 等人 (Miki & Santi, 2001;Santi, Hornyak, & Miki, 2003;Santi, Ross, Coppa, & Coyle, 1999, Santi, Stanford, & Coyle, 1998Santi, Weise, & Kuiper, 1995)的研究发现, 听觉-实时距、听觉-空时距和 视觉-空时距的保持都呈现出"选长"效应。最近 (Spetch & Wilkie, 1983)。后来, Spetch 和 Rusack(1989, 1992 (Zentall, 1999(Zentall, , 2007; 当延迟时间和 ITI 时间更可区分时, "选短"效应会减少或消除 (Zentall, Klein, & Singer, 2004)。另外, 当延迟期间和刺激时距很相似时, 被 试可能从标准刺激呈现开始计时到延迟时间结束 才停止 (Zentall & Kaiser, 2005) Wearden & Culpin, 1998;Wearden & Ferrara, 1993;Wearden, Goodson, & Foran, 2007;Wearden, Parry, & Stamp, 2002) 在若干研究中要求被试判断比较 时距与标准时距的长度关系(相等或长短关系), 而 Droit-Volet 等人(2007)研究中的时间泛化任务只要 求被试判断比较时距是否与标准时距相等。所以前 者可能会更敏感地感觉到标准时距的变化。另外, 毫秒和秒以上时距加工机制的差异 (Lewis & Miall, 2003a, 2003bRammsayer & Lima, 1991) Zentall, 1999Zentall, , 2007)。以记忆消退为基础的主观缩 短假设 (Spetch & Wilkie, 1983)与主观变长相矛盾。 本研究认为, 相对时距假设 (Spetch & Rusack, 1989, 1992 parison was longer, shorter, or of the same duration as the standard duration.…”
unclassified